2022
DOI: 10.1039/d2na00362g
|View full text |Cite
|
Sign up to set email alerts
|

High-surface-area activated carbon from pine cones for semi-industrial spray deposition of supercapacitor electrodes

Abstract: High surface area carbons are so far the best materials for industrial manufacturing of supercapacitor electrodes. Here we demonstrate that pine cones, abundant bio-precursor currently considered as a waste in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The maximum energy density can reach up to 70.78 W h kg −1 at a power density of 1.2 kW kg −1 , and a high energy density of 62.22 W h kg −1 can still be reached even at an ultrahigh output power density of 24 kW kg −1 , which is considerably higher than those of commercially activated carbon-based supercapacitors (3-5 W h kg −1 ) and other previously reported biomass-derived heteroatomdoped carbonaceous symmetric supercapacitors. [71][72][73] It is well known that the energy density is suppressed with the increase of current density since the limited pores on the surface are accessed by electrolyte ions for fast discharging at high current density, whereas almost all pores could be utilized at a low current density. Such superior energy/power characteristics can be ascribed to the optimized stacked architecture and tunable pore conguration of electrode materials as well as the enhancement of the transmission of K + and OH − ions inside the material.…”
Section: Electrochemical Behavior Of the Supercapacitormentioning
confidence: 99%
“…The maximum energy density can reach up to 70.78 W h kg −1 at a power density of 1.2 kW kg −1 , and a high energy density of 62.22 W h kg −1 can still be reached even at an ultrahigh output power density of 24 kW kg −1 , which is considerably higher than those of commercially activated carbon-based supercapacitors (3-5 W h kg −1 ) and other previously reported biomass-derived heteroatomdoped carbonaceous symmetric supercapacitors. [71][72][73] It is well known that the energy density is suppressed with the increase of current density since the limited pores on the surface are accessed by electrolyte ions for fast discharging at high current density, whereas almost all pores could be utilized at a low current density. Such superior energy/power characteristics can be ascribed to the optimized stacked architecture and tunable pore conguration of electrode materials as well as the enhancement of the transmission of K + and OH − ions inside the material.…”
Section: Electrochemical Behavior Of the Supercapacitormentioning
confidence: 99%
“…The one step procedure results in materials with signicantly smaller surface area (<2000 m 2 g −1 ). 49,52 Using ethanol as solvent for KOH is justied by rapid evaporation and more homogeneous distribution of KOH in the powder biochar sample.…”
Section: Materials Preparationmentioning
confidence: 99%
“…Recently we demonstrated that KOH activation tuned previously for preparation of “activated graphene” could be used to produce AC with similarly high BET SSA of about ∼3000 m 2 g −1 starting from pinecone biochar. 49 The pinecone AC showed similar to “activated graphene” pore size distribution and good performance in supercapacitor electrodes produced by both pellet forming and spray deposition 49 using aqueous dispersions. 50,51…”
Section: Introductionmentioning
confidence: 97%
“…GO with a prominent number of holes and defects on the surface). 17,26–28 The number of carbonyl and carboxylic groups, mainly located at the defect edges, increased directly with the number of holes. 17…”
Section: Introductionmentioning
confidence: 99%
“…GO with a prominent number of holes and defects on the surface). 17,[26][27][28] The number of carbonyl and carboxylic groups, mainly located at the defect edges, increased directly with the number of holes. 17 The key role of surface chemistry in the adsorption properties is also proved by the studies of selectivity and efficiencies of functionalized graphene-based sorbents, in comparison with unmodified graphene.…”
Section: Introductionmentioning
confidence: 99%